If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 + -5 = 2x Reorder the terms: 3 + -5 + 4x = 2x Combine like terms: 3 + -5 = -2 -2 + 4x = 2x Solving -2 + 4x = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -2 + 4x + -2x = 2x + -2x Combine like terms: 4x + -2x = 2x -2 + 2x = 2x + -2x Combine like terms: 2x + -2x = 0 -2 + 2x = 0 Add '2' to each side of the equation. -2 + 2 + 2x = 0 + 2 Combine like terms: -2 + 2 = 0 0 + 2x = 0 + 2 2x = 0 + 2 Combine like terms: 0 + 2 = 2 2x = 2 Divide each side by '2'. x = 1 Simplifying x = 1
| 4(y-5)(2y+3)=0 | | 26+(-16)+4= | | 11+3y=14 | | -(7x+3)-(-6x-8)=2 | | -1y=-20 | | 2p^2+4p-1=7p^2-7p+1 | | -3(4x-1)-3=-2(9x+11)-2 | | 1/4(x-3/8)=1/8 | | 3(2x+5)=2(3x-4) | | 1d/4=-2/4 | | -7+5y=-16 | | 3(3x-6)-18=-3(5x+5)-4 | | -9=-3y-7x | | -8x-y=-6 | | 0.3x+3.8=x | | 33.8-32= | | -9x+3y=9 | | -7x+5=-16 | | 1/9c+36=7/9c+5 | | -2+x/3=5 | | -30=5a | | 6(7b-7)=-4+4b | | y=0.8x+3 | | 2/3(12-3h)=h | | 7d+4d-6d+2-8=2d | | 3y=-4x+12 | | -7(1+2x)=23-8x | | -3(3x-6)-18=-3(5s+5)-4 | | -4(1+7m)=30+6m | | n=250/100(2) | | 4(k-9)+18=6 | | -8a^2-6a+9=0 |